(untitled) (CIPEEX, 2026)
INTRODUCTION: Hyperbaric oxygen therapy (HBOT) is a treatment performed in a hyperbaric chamber, in which the patient breathes oxygen at a pressure higher than atmospheric. This condition increases the partial pressure of oxygen dissolved in plasma, enhancing its diffusion into tissues and optimizing cellular oxygenation. HBOT is used as an adjuvant therapy in several acute and chronic conditions, including the treatment of diabetic foot, osteomyelitis, and chronic wounds, among others. OBJECTIVE: To evaluate the clinical progression of the healing process in patients undergoing hyperbaric oxygen therapy at a burn hospital in the city of Anápolis, Goiás, from August 2023 to December 2023. METHODS: This was a cross-sectional, observational, and descriptive study with a retrospective approach, based on data obtained from the medical records of patients who sought medical care at the Burn Hospital of Anápolis-GO. Data collection was carried out through a structured questionnaire. RESULTS: The findings showed that the majority of the sample consisted of men, with diabetes mellitus as the predominant comorbidity among participants. Patients followed a treatment protocol ranging from 6 to 10 sessions, performed within a period of 1 to 6 months. Furthermore, clinical evolution demonstrated that HBOT assists in reducing inflammation and infection, in addition to promoting improvement in the healing process. CONCLUSION: Therefore, the relevance of hyperbaric oxygen therapy as an adjunct strategy in the management of complex wounds is evident, as it contributes not only to lesion improvement but also to enhancing patients’ quality of life.